Hepatic Epithelioid Angiomyolipoma Treated with Laparoscopic Resection: Case Report and Review of the Literature. (1st July 2019) - Williams, Chloe H.; Hickle, Kelli; Bakke, Katherine; Jamshed, Sarah; Bozorgzadeh, Adel
Abstract : Hepatic angiomyolipoma is a rare primary liver tumor, with a radiographic appearance very similar to hepatocellular carcinoma. We present the case of a noncirrhotic patient with a liver tumor suspicious for HCC by imaging features. Liver biopsy demonstrated angiomyolipoma, and the patient successfully underwent a laparoscopic liver resection.